Anatomical Modularity of Verbal Working Memory? Functional Anatomical Evidence from a Famous Patient with Short-Term Memory Deficits - Paulesu, Eraldo; Shallice, Tim; Danelli, Laura; Sberna, Maurizio; Frackowiak, Richard S. J.; Frith, Chris D. (Frontiers in Human Neuroscience, 2017)
Cognitive skills are the emergent property of distributed neural networks. The distributed nature of these networks does not necessarily imply a lack of specialization of the individual brain structures involved. However, it remains questionable whether discrete aspects of high-level behaviour might be the result of localised brain activity of individual nodes within such networks. The phonological loop of working memory (PhL), with its simplicity, seems ideally suited for testing this possibility. Central to the development of the PhL model has been the description of patients with focal lesions and specific deficits. As much as the detailed description of their behaviour has served to refine the PhL model, a classical anatomoclinical correlation approach with such cases falls short in telling whether the observed behaviour is based on the functions of a neural system resembling that seen in normal subjects challenged with PhL tasks or whether different systems have taken over. This is a crucial issue for the cross correlation of normal cognition, normal physiology and cognitive neuropsychology. Here we describe the functional anatomical patterns of JB, a historical patient originally described by Warrington et al (1971), a patient with a left temporo-parietal lesion and selective short phonological store deficit. JB was studied with the H215O PET activation technique during a rhyming task, which primarily depends on the rehearsal system of PhSTM. No residual function was observed in the left temporo-parietal junction, a region previously associated with the phonological buffer of working memory. However, Broca's area, the major counterpart of the rehearsal system, was the major site of activation during the rhyming task. Specific and autonomous activation of Broca's area in the absence of afferent inputs from the other major anatomical component of the phonological loop shows that a certain degree of functional independence or modularity exists in this distributed anatomical-cognitive system.